Evaluasi Anggaran Program Peningkatan Sarana Dan Prasarana Aparatur Di Sekretariat DPRD Kota Bandung Tahun 2018-2020 - Shita Auliya Febriani; Khaerul Umam; Dedeng Yusuf Maolani (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2022)
This research was motivated by the realization of the budget at the Secretariat DPRD City Of Bandung in 2018-2020 which had not yet reached the budget target that had previously been set. This study aims to find out how the effectiveness, efficiency, adequacy, leveling, responsiveness, and accuracy refer to William N. Dunn's theory in planning and managing the budget of the Apparatus Facilities and Infrastructure Improvement Program in the Secretariat DPRD City Of Bandung. The method in this study is a descriptive method based on a qualitative approach. Data collection techniques used by researchers are through interviews, observation, and documentation. Based on the research that the researcher has done, it is found that the budget for the Apparatus Facilities and Infrastructure Improvement Program in the Secretariat DPRD City Of Bandung has been carried out well although there are still some problems that occur both in procurement and maintenance. activities in the program, namely the budget is not fully realized, inaccurate in determining the unit price of goods so that the realization does not reach the target, as well as sudden needs from members of the Council resulting in a budget shortage because what is needed is not listed in the pure budget.